2019
DOI: 10.1093/ee/nvz151
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Mediated Competition Between the Invasive Larger Grain Borer (Coleoptera: Bostrichidae) and the Cosmopolitan Maize Weevil (Coleoptera: Curculionidae)

Abstract: Interspecific competition between agricultural pests may affect the species that can establish, and may also affect food production. Prostephanus truncatus (Horn), the larger grain borer, is endemic to Central America, but invaded Africa with disastrous consequences for maize production. Its main competitor is Sitophilus zeamais Motschulsky, the maize weevil, which is cosmopolitan. These insects co-occur in many regions of the world and both are threats to maize. However, the impact of competition between thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…Indeed, an increasing amount of research has demonstrated the importance of stored-product arthropods in mediating the mycoflora present in postharvest environments. For example, feeding by insects such as Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) on grain kernels was shown to provide a favorable environment for the growth of F. verticillioides , as well as promote the production of fumonisin B1 [ 53 , 54 ]. Hotspots of insect infestation in stored grain may significantly elevate the moisture and temperature in the environment, leading to microbial growth and deterioration of the durable commodities [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increasing amount of research has demonstrated the importance of stored-product arthropods in mediating the mycoflora present in postharvest environments. For example, feeding by insects such as Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) on grain kernels was shown to provide a favorable environment for the growth of F. verticillioides , as well as promote the production of fumonisin B1 [ 53 , 54 ]. Hotspots of insect infestation in stored grain may significantly elevate the moisture and temperature in the environment, leading to microbial growth and deterioration of the durable commodities [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This explains our results in the second half of the storage season when insect grain damage and dust quantities had increased. In laboratory experiments conducted with P. truncatus and S. zeamais, it was observed that the latter was AUTHORS ACCEPTED MANUSCRIPT more competitive at lower temperature while the former was responsible for more damage and produced more progeny as temperature rose above 30°C to 35°C (Quellhorst et al, 2019). Similar results were observed in experiments involving P. truncatus and R. dominica with a further observation that that in an enclosure, P. truncatus outcompetes R. dominica in the 30°C to 35°C temperature range, more likely due to P. truncatus having comparatively higher preference for maize grain as a food source than direct competition (Sakka and Athanassiou, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the recent observations revealed certain beneficial interactions not only between primary and secondary colonisers but also between primary colonizers such as P. truncatus , R. dominica , and Sitophilus spp. (Athanassiou et al ., 2017; Kavallieratos et al ., 2017; Quellhorst et al ., 2020). Frass was also listed among the possible supportive interspecific ecological mechanisms among populations of primary colonisers (Kavallieratos et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of integrated and holistic approaches for commodity protection (Jayas et al ., 1995; White, 1995; Arbogast and Throne, 1997), there has been significant renewed interest in interspecific interactions. Negative interactions, such as predation, parasitism, and competition, are a particular focus of research (Lukas et al ., 2007; Athanassiou et al ., 2017; Quellhorst et al ., 2020). However, interspecific interactions are not necessarily negative.…”
Section: Introductionmentioning
confidence: 99%